A client-centered perspective on 'psychopathology'. (2nd January 2017) - Bohart, Arthur C.
ABSTRACT: I present a client-centered perspective on psychopathology. People have a natural capacity for self-regeneration, self-healing, intelligent functioning, and self-organizing wisdom. Psychopathology occurs when various factors get in the way of people productively utilizing that capacity. Conditions of worth are a major factor. Conditions of worth are ubiquitous, not just occurring in early childhood. We need to change society in order to change psychopathology.